Exploring EFL Students' Speaking Skill Development through Digital Social Media for Two Universities in South Sulawesi - Areski Wahid (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The current research aimed at analyzing the EFL students' speaking skill development through digital social media inside university context. Many researchers conducted their research outside universities but it is still rare to explore existing aspects, both inside university. The study design used the ethnographic study. The study was conducted at two Indonesian universities. Universitas Muhammadiyah Parepare (UMPAR), located in Parepare, and Universitas Muhammadiyah Sidenreng Rappang (UMS Sidrap), located in Sidrap, South Sulawesi. The subjects of this study were three lecturers and six students who are familiar with using digital social media in speaking development. The data collection methods were observations, lecturers’ interviews and students interviews. The techniques for analyzing data in ethnographic research are descriptive labels, selecting, identifying, generalizing, and noting. This study showed that in speaking development, several social media platforms inside universities were utilized in their teaching and learning process. The students developed their speaking skill development through digital social media in some ways in universities context: making appointments with strict guidelines, adapting speaking activities to different learning styles with the help of digital social media in classroom and understanding the function of digital social media in developing speaking skills for the students in classroom.